SOLUSI NUMERIK SISTEM PERSAMAAN NON LINEAR DALAM REAKSI STEAM REFORMING MENGGUNAKAN METODE NEWTON-RHAPSON: Numerical Solution of Non-Linear Equation System in Steam Reforming Reaction Using Newthon-Raphson Method - Kirani, Azizah Fitrah; Ibnas, Risnawati; Syata, Ilham (Yayasan Al-Amin Qalbu, 2025)
This study discusses the solution of a system of non linear equation from the steam reforming reaction which consist of two non-linear equation with two variables, namely the and variables which will be solved using the Newton-Raphson method. The results of the final iteration are obtained with a value of x is 0,754090792 and y is 0,700893797. These two values will be substituted into the mole fraction formula to find the equilibrium composition of the steam reforming reaction components. The research results were obtained by formulating the mole fraction of each component of a chemical compound that had been formulated, then the value of the mole fraction for each component of the chemical compound was obtained, the value of the mole fraction for CO = 0,00462, H2 = 0,25745, CO2 = 0,06089, H2O = 0,56875 and CH4 = 0,10827. Based on the results obtained, it can be concluded that the Newton-Raphson method can be applied to find the equilibrium composition of the components of the steam reforming reaction.